„Folyékony örökség”. A marrákesi VI. Mohamed Víz Múzeumban - Fülöp, Zoltán Ottó (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
For the challenges of postcolonial existence in Morocco, being addressed as social organizing factor in the culture, answers are being searched at local, national and global levels. The Museum Mohammed VI for the Water Civilization in Marrakech plays a key role in the conservation and presentation of water supply as natural resource based on material culture. This museum presents the historical and cultural role of water, the diversity of social and spiritual contents associated with it, distinctly the traditional paradigms of representation. The cultural center tries to get involved in the international museum circulation, open to new possibilities of architectural solutions, visual tools and arranging of exhibitions. According to the curator’s choice, the main task is to preserve the memories of the past and by reinterpreting those with exhibiting activities reflecting the heritage. The staging of water conservation is realised by using interactive techniques and provides a reflexive experience for visitors. Who is receptive to historical, cultural anthropological approaches may feel addressed, in the meantime the visitor who is interested in technical sciences, geography, geopolitics and applied chemistry finds his account in the exhibition. The innovative museum is an integral part of Al Hamra’s tourism and cultural industry, even as the Tiskiwin Museum, which reflects the museum anthropological perspective, located in the medina. The two memory institutions also illustrate the diversity of the city’s cultural image.